Prenatal diagnosis of generalized arterial calcification of infancy in the second trimester. (5th October 2022) - Pu, Lihong; Dai, Xiaohui; Liu, Hanmin; Li, Lei; Zhao, Fumin; Chen, Jiao
Abstract: Objectives: Generalized arterial calcification of infancy (GACI) is a rare autosomal recessive disorder characterized by subintimal fibrous proliferation and deposition of calcium salts in the internal elastic lamina, leading to extensive arterial calcification and stenosis of large and medium‐sized arteries. Prenatal diagnosis is usually made in the third trimester by detection of aortic and pulmonary calcification with associated nonimmune hydrops; earlier prenatal diagnosis is rare. This study was performed to examine the prenatal ultrasound and genetic features of fetuses with GACI. Methods: We retrospectively reviewed the ultrasound findings, their progression in utero, and the clinical features in three fetuses with GACI ascertained using ultrasound in the second trimester. GACI was subsequently confirmed through pathological examination and/or molecular genetic testing. Results: All three fetuses had hyperechogenic valves or annuli as the first detectable manifestation in the second trimester, followed by relatively rapid progression to arterial wall calcification. Three novel mutations of the ENPP1 gene associated with GACI were found in two of the cases (c.26dupG, c.1454A > G, and c.263C > G). Conclusions: GACI should be suspected when hyperechogenic cardiac valves, annuli, or arterial walls are noted after ruling out other causes of arterial calcification. Genetic testing is important for prenatal and future preimplantation genetic diagnosis. Key points: What's already known about this topic? Historically, generalized arterial calcification of infancy (GACI) has often been diagnosed retrospectively. Prenatal diagnosis is usually made in the third trimester by the detection of calcifications in the aortic, pulmonary, and other large arterial walls, with associated nonimmune hydrops in some cases. What does this study add? We present three cases of GACI diagnosed prenatally using ultrasound in the second trimester, in which hyperechogenic valves and/or annuli were the early manifestation. We also report three novel mutations of the ENPP1 gene associated with GACI.